Kinetic and reaction engineering model for thermal solution of oil shale in FCC decant oil - Patzer, John F.; Moon, William G.; Jones, Gary L.; King, A.Bruce (Chemical engineering science, 1986)
Fundamental reaction kinetics and reaction stoichiometry are developed for thermal solution of oil shale based upon analysis of data from 67 runs on a once-through, continuous stirred-tank reactor (CSTR) bench-scale unit using FCC decant oil as the solution medium. A material-balanced model of the CSTR is used in conjunction with nonlinear optimization theory to derive estimates of the kinetics parameters and stoichiometric coefficients. Reactions occur in the liquid phase and are of two basic types: thermal conversion of kerogen to form heavy oil and cracking of the liquid oils to form lower boiling oils, gases, and residue, i.e., coke. The reaction paths, described in terms of pseudocomponents which lump narrow boiling range cuts of oil, involve a cascading series of reactions in which components in each boiling range cut undergo first-order cracking to form components in lower boiling ranges. Each reaction rate is expressed in terms of the classical Arrhenius temperature dependence multiplied by the concentration of the pseudocomponent boiling cut. Concentration dependence is first-order for all psuedocomponents. The kerogen decomposition rate parameters are comparable to literature values for conventional pyrolysis approaches. Model predictions for kerogen conversion and product yield structure agree well with the experimental data.